Analisis Gaya Kepemimpinan dalam Manajemen Sekolah di SMA Katolik Makale - Alfonsius Atok Nahak; Dina Ramba; Yohanis Lotong Ta’dung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze leadership styles in school management at Makale Catholic High School. This research uses qualitative descriptive. Results: The results of the analysis show that Makale Catholic High School still needs facilities/infrastructure in the teaching and learning process. The leadership style applied by the principal at Catholic High School is the Democratic leadership style. In the results of the analysis, it was found that in school management it was found that school facilities/infrastructure in supporting the learning and extracurricular processes were generally inadequate. The results of the research are to determine the management of Makale Catholic High School in organizing various academic activities such as Try Outs, National Examinations and other extracurricular activities so that Makale Catholic High School's achievements increase. Suggest to Makale Catholic High School to plan and provide adequate facilities/infrastructure to be able to answer needs in the teaching and learning process.